Nonlinear theory of successions in forestry biogeocenoses: mathematical aspects - Chernyshenko, S. V.; Chernyshenko, V. S.; Alekseyev, M. O. (My University, 2011)
Systems analysis of biological phenomenon of succession has been carried out. The history of the subject and the current state of art are considered. Classification of both succession process as a whole and separate succession stages are proposed. Interaction between two main gears of succession – competition between plant species and their interaction with abiotic part of the biogeocoenose – are considered. Extreme nature of succession process and polygenetic structure of biogeocoenose, as a result of succession, are demonstrated.
Keywords: biogeocoenose, succession, systems analysis, woodland, mathematical model